Family business in Argentina: The discreet charm of strong ties in weak institutional contexts - Alejandro Gaggero (economic sociology. perspectives and conversations, 2023)
In Latin America, most important local companies are part of business groups controlled by families. Data show that a significant part of the business elite is organized under rather concentrated equity structures, with a lower share of institutional financial investors than those in developed countries (Aldrighi and Postali 2010; Lefort 2005). There is little resemblance to the situation in the Anglo-Saxon world, where most leading companies go public and their equity is in the hands of thousands of shareholders.
Keywords: 300